Fyodor Dostoevsky - Conradi, Peter J., 1945- (Macmillan, 1988)
An examination of Dostoevsky's understanding of psychological "doubleness". Referring to the four major novels, the author illustrates how Dostoevsky's understanding of suffering, guilt, repentance, paranoia and religious terrors has proved relevant in today's unbelieving age.